Relationship of Intrinsic and Extrinsic Factors to The Incidence of Diarrhea in Toddlers Noelbaki Village District - Stefania mentari kenda; Mustakim Sahdan; Amelya B Sir (Universitas Nusa Cendana, 2022)
Diarrhea is a health problem throughout the world. Diarrhea is an infectious disease that causes infant mortality. Data on diarrhea cases in Noelbaki Village, Central Kupang District, Kupang Regency, in 2017 found 42 cases; in 2018, 53 cases; and in 2019, 57. This research intends to determine the Intrinsic and Extrinsic Factors in the Incidence of Diarrhea in Toddlers in Noelbaki Village, Kupang Regency. This type of research is quantitative through an observational approach using a cross-sectional design. The population in this study amounted to 210 people, and the sample used was 67 people. Data were analyzed using chi-square with the level of interpretation = 0.05. The research concludes that exclusive breastfeeding (0.017) and hand washing with soap (0.000) have a relationship with diarrhea in toddlers. In contrast, nutritional status (0.234) has no connection with diarrhea in toddlers. Health workers should improve services and counseling about exclusive breastfeeding and washing hands with soap so that people always care and remember the importance of health for their children.